Digital Public Service Implementation through the SiKawan Cloud Office System: Evidence from a Village Government in Banyuwangi, Indonesia - Safrieta Suyitno; Tjandra Yunfha; Erna Agustina (Contemporary Public Administration Review, 2026)
The rapid advancement of digital government has encouraged public organizations to transform conventional administrative practices into technology-driven public service delivery. In Indonesia, the implementation of the Electronic-Based Government System (SPBE) has become a strategic policy to improve the quality, efficiency, transparency, and accountability of public services, including at the village government level. This study aims to examine the implementation of digital public services through the SiKawan (Cloud Office System) application at the Kedayunan Village Office, Banyuwangi Regency, Indonesia. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving village officials, system administrators, and service users. The findings reveal that the successful implementation of SiKawan is influenced by four interrelated dimensions of policy implementation: communication, organizational resources, implementers' commitment, and bureaucratic structure. The system has significantly enhanced administrative efficiency by reducing service processing time, improving document management, strengthening inter-agency coordination, and enabling digital document authentication through electronic signatures. Nevertheless, several challenges remain, including limited digital competencies among village officials, inadequate technological infrastructure, and resistance to organizational change. This study contributes to the literature on digital government by providing empirical evidence of cloud-based public service implementation within village governance, a context that remains underexplored in developing countries. The findings offer practical insights for policymakers in designing sustainable digital transformation strategies to strengthen local governance and improve citizen-centered public service delivery.